2009
DOI: 10.1038/ejcn.2009.96
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum 25-hydroxyvitamin D and depressive symptoms in Japanese: analysis by survey season

Abstract: Both depressive symptoms and vitamin D insufficiency are common during winter. This study examined the association between serum 25-hydroxyvitamin D and depressive symptoms by survey season. Subjects were 527 municipal employees aged 21-67 years of two municipal offices in Japan. Overall, there was no measurable association. However, in the workplace surveyed in November, multivariate-adjusted odds ratios (95% confidence interval) of having depressive symptoms (Center for Epidemiologic Studies Depression score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 10 publications
1
48
0
1
Order By: Relevance
“…Analyses showed an inverse association between vitamin D concentrations and levels of depressive symptoms but no effect modification by season (interaction term: p=0.39). Similarly, although using different methods, a study of 527 office workers in Japan aged 21 to 67 years (Nanri et al, 2009) Conflicting results found across previous studies are likely to be underpinned by diverse study methodology. Several differences including the observed population and age groups, definitions of seasons, heterogenity in instruments used to assess depressive symptoms, and various methods to analyse vitamin D and cut-offs to determine depression and vitamin D deficiency make direct comparisons with previous studies challenging.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Analyses showed an inverse association between vitamin D concentrations and levels of depressive symptoms but no effect modification by season (interaction term: p=0.39). Similarly, although using different methods, a study of 527 office workers in Japan aged 21 to 67 years (Nanri et al, 2009) Conflicting results found across previous studies are likely to be underpinned by diverse study methodology. Several differences including the observed population and age groups, definitions of seasons, heterogenity in instruments used to assess depressive symptoms, and various methods to analyse vitamin D and cut-offs to determine depression and vitamin D deficiency make direct comparisons with previous studies challenging.…”
Section: Discussionmentioning
confidence: 64%
“…Remarkably, relatively few studies have examined the influence of season on the association between vitamin D and depression (Brandenbarg et al, 2012;Hoang et al, 2011;Kjaergaard et al, 2011;Nanri et al, 2009;Stewart and Hirani, 2010). Results from these studies were mixed; three studies did not observe an influence of season (Brandenbarg et al, 2012;Nanri et al, 2009;Stewart and Hirani, 2010), while the other two studies reported conflicting evidence for an inverse association between vitamin D and depressive symptoms in winter (Hoang et al, 2011) and in summer (Kjaergaard et al, 2011).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…This subset analysis may shed light on why there were conflicting results in earlier studies because the populations were not assessed on the basis of prior history of depression. [20][21][22][23][24] These findings may potentially have clinical importance in the evaluation of patients with a prior history of depression.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Previous observational studies also used the CES-D to assess depressive symptoms in large populations. [20][21][22][23][24]31 History of depression was based on patient report and confirmed by the physician but not further defined. In addition, although we controlled for many known confounds, some may have remained.…”
Section: Discussionmentioning
confidence: 99%